Maternal hypertensive mother's knowledge, attitudes and misconceptions on hypertension in pregnancy: A multi-center qualitative study in Ghana - Evelyn Tamma; Kwame Adu-Bonsaffoh; Adanna Nwameme; Phyllis Dako-Gyeke; Emmanuel Srofenyoh; Joyce Browne (Public Library of Science (PLoS), 2023)
Hypertension in pregnancy is one of the commonest complications of pregnancy and a leading cause of maternal and perinatal morbidity and mortality globally, with the highest burden in low and middle income countries. Pregnant women's knowledge about hypertension in pregnancy facilitates early health seeking behavior, which can result in early diagnosis and treatment. This study therefore explored the knowledge, misconceptions and attitudes of Ghanaian women who were affected by hypertension in pregnancy. A qualitative study was carried out across five referral hospitals in the Greater Accra Region of Ghana. In-depth interviews (IDIs) and focus group discussions (FGDs) were used to explore the women's knowledge on hypertensive disorders of pregnancy (HDP), and particularly preeclampsia. Women of at least 16 years, admitted with a HDP to the maternity ward with gestational ages from 26-34 weeks were eligible for participation. The inductive approach was used to develop a code book and the dataset was coded using Nvivo version 12 software. A total of 72 women participated in the study. Fifty IDIs and 3 FGDs involving 22 women were conducted. Although most of the women had regular antenatal visits, several had never heard of "pre-eclampsia". More common terminology used by women (i.e. "Bp") referred to any of the hypertensive disorders (e.g. pre-eclampsia, gestational hypertension and chronic hypertension). Women also perceived that pre-eclampsia may be inherited or caused by "thinking too much". The study revealed that the knowledge about hypertension in pregnancy is limited among the affected women despite regular antenatal attendance with some form of health education. There should be more education programs on hypertensive disorders of pregnancy including pre-eclampsia with revised strategies.